Analisis Kritis terhadap Isu Negatif Abu Hurairah dan Ibnu Abbas dalam Israiliyyat - Rozikin, Ahmad Khoirur (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2018)
Israiliyyat is a story told by ahl al-Kitab, Jewish and Christian, whether the story derives from their Holy Book or popular story from generation to generation.Some friends of Rasulullah saw. asked to ahl al-Kitab when they have not been understood some meanings of al-Quran, the most question is the story of past people, that not explained in detail in al-Quran. In the meaning of the question not related with aqidah of Islam. If the question related with aqidah of Islam, some friends of Rasulullah filtering what ahl al-Kitab said, because of a negative side from the ahl al-Kitab.Questions of friends of Rasulullah become an issue, then the enemy of Islam said that some friend of Rasulullah doesn‟t consist to holding message from Rasulullah who ever warn not to ask to ahl al-Kitab. Some friends who asked to ahl al-Kitab is Ibnu Abbas and Abu Hurairah.Ignaz Goldziher dan Abu Rayyah is two people who said that Ibnu Abbas and Abu Hurairah not consist with message from Rasulullah. So, the credibility of Ibnu Abbas and Abu Hurairah could be doubt.